The 100 most cited articles in zebrafish: a bibliometric perspective - Mohd Nasir, Mohd Hamzah; Abdul Aziz, Salmi; Jusoh, Abdul Rashid; H. Ahmad, Asma; Othman, Zahiruddin; Ahmi, Aidi; Zakaria, Rahimah (The Egyptian Society for the Development of Fisheries and Human Health (ESDFHH), 2021)
The 100 most cited articles in zebrafish were published between 1990 and 2015, with 70% published after 2000. The most cited article received 7379 citations, while the least received only 405. The 100 most cited articles were published in 39 different journals with Development having the highest citations (n = 11,966) as well as the highest total publications (n=21). Eighteen authors listed four or more articles, while the USA was found to be the most prolific country, producing 81 articles, and having the most affiliated institutions and the top research funders. The most frequent keywords were “zebrafish” followed by “Danio rerio”, “blastula”, “cleavage”, “embryogenesis”, “mesoderm”, “notochord”, and “somitogenesis”. This bibliometric data render a historical perspective on the advancement of zebrafish research and facilitate mapping potential authors, institutions, and countries for future collaborations as well as important key topics for future research.